Assessment of the ability of HPV vaccines to induce neutralizing antibodies based on pseudovirus-based neutralization assay - Wu, Zhihua; Li, Xuejie; Zhang, Beibei (Frontiers in Public Health, 2025)
IntroductionHuman papillomavirus (HPV) infection represents a significant public health concern due to its strong association with various cancers and other diseases. The development and implementation of prophylactic HPV vaccines, including bivalent, quadrivalent, and nonavalent formulations, have markedly reduced the incidence of these diseases by inducing the production of neutralizing antibodies. The detection and characterization of neutralizing antibodies against HPV are essential for understanding immune responses and evaluating vaccine efficacy. However, limited data are available on neutralizing antibody levels following vaccination with different HPV vaccines in the Chinese population. This study aimed to evaluate neutralizing antibody responses in individuals vaccinated with HPV vaccines.MethodsEighty-four female vaccine recipients were enrolled. Neutralizing antibody responses were assessed using a pseudovirus-based neutralization assay (PBNA). Serum samples were analyzed for the presence and titers of neutralizing antibodies against HPV types 6, 11, 16, 18, 31, 33, 45, 52, and 58.ResultsThe study revealed variations in neutralizing antibody levels across different HPV subtypes. The PBNA demonstrated high reproducibility and reliability in measuring these responses.DiscussionThese findings highlight the utility of PBNA as a robust tool for assessing immune responses to HPV vaccination and optimizing vaccine strategies. The study provides valuable insights into the neutralizing antibody responses elicited by HPV vaccines in the Chinese population.